Effects of procalcitonin-guided treatment on antibiotic use and need for mechanical ventilation in patients with acute asthma exacerbation: Meta-analysis of randomized controlled trials - Wanis H. Ibrahim; Kamran Mushtaq; Tasleem Raza; Anand Kartha; Ahmed O. Saleh; Rayaz A. Malik (International Journal of Infectious Diseases, 2017)
Objective: The primary outcome was to determine whether serum procalcitonin-guided antibiotic therapy can reduce antibiotic exposure in patients with an acute exacerbation of asthma presenting to the primary care facility or emergency department, or during hospital admission. The secondary outcome was the need for mechanical ventilation. Methods: An extensive literature search was performed to identify randomized controlled clinical trials (published in English) that compared serum procalcitonin-guided antibiotic therapy versus antibiotic use according to physicianâs discretion for adult participants with mild, moderate, or severe acute asthma exacerbations. Results: Four randomized controlled trials evaluating 457 patients were included in this meta-analysis, with significant homogeneity observed among these studies. Procalcitonin-based protocols decreased antibiotic prescriptions (relative risk 0.58, 95% confidence interval 0.50â0.67). The conclusion regarding the difference between the two groups in the need for mechanical ventilation (relative risk 1.10, 95% confidence interval 0.62â1.94) was guarded due to inadequate power and the potential for type II error. The overall quality of evidence was also limited by the lack of double-blinding. Conclusions: These data suggest a potential benefit for the use of serum procalcitonin in guiding antibiotic therapy in patients with an acute asthma exacerbation and advocates the need for more randomized controlled trials. Keywords: Procalcitonin, Asthma, Antibiotic, Exacerbation, Guided